Diminishing seasonality of subtropical water availability in a warmer world dominated by soil moisture–atmosphere feedbacks - Sha Zhou; A. Park Williams; Benjamin R. Lintner; Kirsten L. Findell; Trevor F. Keenan; Yao Zhang; Pierre Gentine (Nature Communications, 2022)
Here, the authors find increased dry–season and decreased wet–season water availability over subtropical regions and the Amazon. This is caused by seasonally varying soil moisture–atmosphere feedbacks under global warming.